Examining stigma dynamics: a scoping review of social network analysis in communicable disease contexts - Baharuddin, Izyan Hazwani; Ismail, Nurhuda; Patterson, Megan S.; Yasin, Siti Munira; Naing, Nyi Nyi; Ibrahim, Khalid (Intelektual Pustaka Media Utama, 2025)
The global COVID-19 pandemic has brought attention to the profound impact of stigma on individuals, communities, and societies. Social network analysis (SNA), based on network theory, offers a transformative approach to investigate the complex interplay of social structures, relationships, and information dissemination in communicable disease contexts. This scoping review aims to examine the utilization of SNA in studying stigma dynamics related to communicable diseases, assess the current research landscape, identify gaps, and highlight key findings. Three databases (Scopus, Web of Science, and PubMed) were searched for studies on SNA and stigma in communicable diseases. From the identified studies, three eligible articles were selected for review, providing insights into the role of stigma as a barrier to social integration, thereby impacting network centrality. The review also explores patterns of stigma communication on social media and examines the impact of interventions on individuals’ social networks. Overall, this review emphasizes the value of SNA in comprehending the intricate relationships between social networks and stigma in communicable disease contexts.